Vision and difference femininity, feminism, and histories of art - Pollock, Griselda (Routledge, 1988)
Griselda Pollock provides concrete historical analyses of key moments in the formation of modern culture to reveal the sexual politics at the heart of modernist art. Crucially, she not only explores a feminist re-reading of the works of canonical male Impressionist and Pre-Raphaelite artists including Edgar Degas and Dante Gabriel Rossetti, but also re-inserts into art history their female contemporaries - women artists such as Berthe Morisot and Mary Cassatt. Pollock discusses the work of women artists such as Mary Kelly and Yve Lomax, highlighting the problems of working in a culture where the feminine is still defined as the object of the male gaze.
Section: 239 p. : ill. ; 24 cm
Keywords: arts; corps; cours; discipline; europe; femmes* artistes; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; représentation des femme*; régions géographiques; thématiques

In other worlds essays in cultural politics - Spivak, Gayatri Chakravorty (Routledge, 1988)
Dans cet ouvrage classique, Gayatri Chakravorty Spivak, l'une des théoriciennes de la culture les plus importantes et les plus influentes travaillant aujourd'hui, analyse la relation entre la langue, les femmes et la culture dans des contextes occidentaux et non occidentaux. Développant une intégration originale de puissantes méthodologies contemporaines - déconstruction, marxisme et féminisme - Spivak tourne ce nouveau modèle sur les grands débats de l'étude de la littérature et de la culture, assurant ainsi que In Other Worlds est devenu un outil précieux pour étudier notre propre monde et celui des autres cultures.
Keywords: 1900-1999; 1980-1989; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; histoire et politique; international; lit3220; premier cycle; périodes historiques; thématiques; théories féministes; théories littéraires; études littéraires; études postcoloniales